THE ROLE OF THE PRINCIPAL'S LEADERSHIP IN IMPROVING QUALITY OF EDUCATION AT STATE MTs 4 KLATEN - WIDAWATI, ARYN; OKTAFIA, NISA; DEWI, KHARISMA SYIFA; LUTHFIAH, VIRA; SUPRIYANTO , SUPRIYANTO (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
This study aims to analyze the leadership role of school principals in improving the quality of education at MTs Negeri 4 Klaten. In context education, effective leadership is a key factor that affects achievement of educational goals. The research method used is qualitative with a case study approach, where data is obtained through interviews and Observation. The results of the study show that the principal plays the role of Visionary leaders, able to motivate and inspire educators and students educate. In addition, the principal also functions as a facilitator in creating conducive learning environment. Improving the quality of education is carried out through careful planning, development of educator competencies, and periodic evaluations to educational programs. Principal leadership doesn't just function as managers, but also as change agents committed to achieve excellence in education. The conclusion of this study emphasizes the importance of the role of school principals in creating a positive educational climate, which in turn will improve the quality of education at MTs Negeri 4 Klaten. ABSTRAKPenelitian ini bertujuan untuk menganalisis peran kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan di MTs Negeri 4 Klaten. Dalam konteks pendidikan, kepemimpinan yang efektif merupakan faktor kunci yang mempengaruhi pencapaian tujuan pendidikan. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus, dimana data diperoleh melalui wawancara dan Observasi. Hasil penelitian menunjukkan bahwa kepala sekolah berperan sebagai pemimpin visioner, mampu memotivasi dan memberi inspirasi bagi pendidik dan mendidik siswa. Selain itu, kepala sekolah juga berfungsi sebagai fasilitator dalam menciptakan lingkungan belajar yang kondusif. Peningkatan mutu pendidikan dilakukan melalui perencanaan yang matang, pengembangan kompetensi pendidik, dan evaluasi berkala terhadap program pendidikan. Kepemimpinan kepala sekolah tidak sekedar berfungsi sebagai manajer, namun juga sebagai agen perubahan yang berkomitmen untuk mencapai keunggulan dalam pendidikan. Kesimpulan penelitian ini menekankan pentingnya peran kepala sekolah dalam menciptakan iklim pendidikan positif yang pada akhirnya akan meningkatkan mutu pendidikan di MTs Negeri 4 Klaten.